2012
DOI: 10.1002/bdra.23005
|View full text |Cite
|
Sign up to set email alerts
|

Association between MTHFR polymorphisms and orofacial clefts risk: A meta‐analysis

Abstract: Electronic literature searches of the PubMed, EmBase, and Medline databases were performed up to October 31, 2011. Fixed-effects or random-effects models were used to calculate the pooled odds ratios (ORs) for two genetic comparisons (heterozygous mutation vs. wild type, homozygous mutation vs. wild type). RESULTS A total of 18 studies were ultimately identified. The pooled results revealed no statistical association between infant and maternal C677T and A1298C variants and risk of cleft lip with or without pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…According to Verkleij-Hagoort et al(2007) [19] and Johnson and Little (2008) [20], no significant associations between MTHFR C677T and A1298C polymorphisms and NSCL/P were acquired. The pooled results of Luo Y et al (2012) [17] indicated that maternal MTHFR 677TT genotype was related to increased risk of having a NSCL/P offspring. The more recently meta-analysis conducted by Pan Y et al (2012) [18] showed that MTHFR C677T polymorphism contributed to elevated risk of NSCL/P among Asians.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Verkleij-Hagoort et al(2007) [19] and Johnson and Little (2008) [20], no significant associations between MTHFR C677T and A1298C polymorphisms and NSCL/P were acquired. The pooled results of Luo Y et al (2012) [17] indicated that maternal MTHFR 677TT genotype was related to increased risk of having a NSCL/P offspring. The more recently meta-analysis conducted by Pan Y et al (2012) [18] showed that MTHFR C677T polymorphism contributed to elevated risk of NSCL/P among Asians.…”
Section: Discussionmentioning
confidence: 98%
“…Since then, a great number of studies have been conducted, but the results were inconsistent [14][16]. In order to elucidate the role of MTHFR C677T and A1298C polymorphisms in NSCL/P, several meta-analyses were performed [17][20], but the relationships especially among Asian subjects remained unclear. Recently, some new case-control studies with large sample size have been published [21]–[23].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, rs1801133 (C677T) polymorphism in MTHFR is the most extensively investigated in NSCL/P in both affected patients and their parents. Although the association between rs1801133 and oral cleft risk is controversial, with some studies showing significant association while others rebutting it (Luo et al, ; Butali et al, ), the studies with the Brazilian population refuted the association of this polymorphism with both maternal and fetal risk for NSCL/P (Gaspar et al, ; Brandalize et al, ; Bufalino et al, ). Revaluating our published data (Bufalino et al, ), we found a linkage equilibrium between rs1801133 and rs2274976 (D′ = 0.10), revealing that the genotypes present at those loci are independent.…”
Section: Discussionmentioning
confidence: 99%
“…MTHFR 667C>T (rs1801133), one of the most highly studied variants with known functional effects on one-carbon metabolism, [3739] had a null offspring association (RR: 0.99, 95% CI: 0.84–1.19) and a weak maternal association (RR: 1.16, 95% CI: 0.97–1.38). Two previous studies of candidate SNPs from folate-related genes identified SLC19A1 80G>A (rs1051266) as positively associated with neuroblastoma in Brazil [40, 41].…”
Section: Discussionmentioning
confidence: 99%